HÜRTHLE-CELL CARCINOMA OF THE THYROID: CLINICOPATHOLOGIC FEATURES AND SURGICAL OUTCOMES AT A SINGLE INSTITUTION - Memon, Muhammad (Sanamed, 2026)
Background: Hürthle cell carcinoma (HCC) is a rare differentiated thyroid malignancy with variable biological behavior. This study evaluates clinicopathologic features, treatment patterns, and long-term outcomes in patients managed at a single tertiary institution.Methods: We retrospectively reviewed medical records of patients with histologically confirmed HCC between January 2005 and December 2020. Demographics, tumor characteristics, surgical treatment, adjuvant radioactive iodine (RAI) therapy, recurrence, and survival were analyzed. Outcomes were compared with reported retrospective series and discussed in the context of current ATA guidelines.Results: Forty-eight patients were identified (mean age, 58.7 ± 11.4 years; female-to-male ratio, 2.2:1). Mean tumor size was 38.5 ± 14.2 mm. Minimally invasive disease was present in 29 patients (60.4%), and widely invasive disease in 19 (39.6%). Total thyroidectomy was performed in 36 patients (75%), and lobectomy in 12 (25%). RAI therapy was administered to 30 patients (62.5%), predominantly in widely invasive cases. Median follow-up was 104 months (range, 24–192 months). Recurrence occurred in 8 patients (16.7%), with a median time to relapse of 78 months. Five- and ten-year overall survival (OS) rates were 91.3% and 81.5%, respectively. Disease-specific survival (DSS) was 95.6% at 5 years and 90.2% at 10 years. Ten-year disease-free survival (DFS) was 82.1%.Conclusions: Our results support existing evidence that minimally invasive HCC carries an excellent prognosis, while widely invasive tumors have a higher risk of recurrence. Long-term follow-up is essential, given the potential for late recurrence. These findings are consistent with current ATA guidelines recommending risk-tailored treatment and surveillance strategies.
Keywords: Hürthle cell carcinoma; thyroid cancer; minimally invasive; widely invasive; recurrence; survival; ATA guidelines